Fa’āliyyah Barnāmaj Ma’rifī Sulūkī li Khafđi al-Idmān ‘alā Mawāqi’al-Tawāṣul al-Ijtimā’ī Lada Țullabāh al-Marḥalah al-I’dādiyyah wa ‘Alāqatih bi Mustawā al-Ta’līmī li al-Walidain: فعالية برنامج نفسي لخفض الإدمان على مواقع التواصل الاجتماعي لدى طلبة المرحلة الإعدادية وعلاقته بمستوى التعليمي للوالدين - Sadeeq, Shaveen Hussein; Omar, Jehan Hussein (Study Program of Arabic Language Teaching, 2025)
The current research aims to study the impact of the effectiveness of a psychological program to reduce social media addiction among preparatory school students and its relationship to parental educational level. The researchers employed a quasi-experimental design on a sample consisting of (23) female students from Media Girls' School in Dohuk Governorate, who were purposively selected from those with high levels of social media addiction. The psycho-educational program consisting of (12) sessions was implemented at a rate of two sessions per week, with each session lasting (45) minutes. The researchers used the Social Media Addiction Scale developed by Younis (2016), consisting of (30) items. The results showed no statistically significant differences in program effectiveness attributed to fathers' or mothers' educational levels, indicating that the effectiveness of the psycho-educational program is not influenced by parental educational level, and that other psychological and social factors may play a more important role in determining the success of therapeutic intervention.